Testosterone Modifies Alterations to Detrusor Muscle after Partial Bladder Outlet Obstruction in Juvenile Mice - Andrew S. Flum; Paula R. Firmiss; Diana K. Bowen; Natalie Kukulka; Grace B. Delos Santos; Robert W. Dettman; Robert W. Dettman; Edward M. Gong; Edward M. Gong (Frontiers Media S.A., 2017)
Lower urinary tract symptoms secondary to posterior urethral valves (PUV) arise in boys during adolescence. The reasons for this have previously been attributed to increased urine output as boys experience increased growth. Additionally, there are few choices for clinicians to effectively treat these complications. We formed the new hypothesis that increased androgen levels at this time of childhood development could play a role at the cellular level in obstructed bladders. To test this hypothesis, we investigated the role of testosterone on bladder detrusor muscle following injury from partial bladder outlet obstruction (PO) in mice. A PO model was surgically created in juvenile male mice. A group of mice were castrated by bilateral orchiectomy at time of obstruction (CPO). Testosterone cypionate was administered to a group of castrated, obstructed mice (CPOT). Bladder function was assessed by voiding stain on paper (VSOP). Bladders were analyzed at 7 and 28 days by weight and histology. Detrusor collagen to smooth muscle ratio (Col/SM) was calculated using Masson's trichrome stain. All obstructed groups had lower max voided volumes (MVV) than sham mice at 1 day. Hormonally intact mice (PO) continued to have lower MVV at 7 and 28 days while CPO mice improved to sham levels at both time points. In accordance, PO mice had higher bladder-to-body weight ratios than CPO and sham mice demonstrating greater bladder hypertrophy. Histologically, Col/SM was lower in sham and CPO mice. When testosterone was restored in CPOT mice, MVV remained low at 7 and 28 days compared to CPO and bladder-to-body weight ratios were also greater than CPO. Histologic changes were also seen in CPOT mice with higher Col/SM than sham and CPO mice. In conclusion, our findings support a role for testosterone in the fibrotic changes that occur after obstruction in male mice. This suggests that while other changes may occur in adolescent boys that cause complication in boys with PUV, the bladder itself responds to testosterone at the cellular level. This opens the door to a new understanding of pathways that influence bladder fibrosis and could lead to novel approaches to treat boys with PUV.